HUBUNGAN KOMPETENSI PUSTAKAWAN DALAM MENGELOLA INLISLITE TERHADAP KUALITAS LAYANAN PERPUSTAKAAN DI SMAN 4 KARAWANG - Azzahra Al-ash, Keysha; Hinggil Permana; Muchdjabir Wahid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
School libraries need competent librarians to turn automation into accurate and responsive services. This study examined the relationship between librarians’ competence in managing INLISLite and library service quality at SMAN 4 Karawang. A quantitative correlational survey involved 189 Grade XI students selected from 357 students through simple random sampling. Data were collected using a valid 30-item four-point Likert questionnaire, observation, and documentation. The instrument obtained a Cronbach’s alpha of 0.968. Descriptive statistics, the Kolmogorov-Smirnov test, and Spearman rank correlation were processed using SPSS 27. Both variables were in the good category. Management competence achieved the highest mean of 3.0095, while Affect of Service reached 3.0053. The data were non-normal. Spearman’s rho was 0.947 with p < 0.001, indicating a positive, significant, and very strong relationship. Effective INLISLite services therefore require managerial, organizational, information-service, and digital competence.